“Pernyataan Kalam” Dalam Naskah Sastra Melayu Klasik - Rias Antho Rahmi Suharjo (Buletin Al-Turas, 2014)
AbstrakPernyataan Kalam merupakan sesuatu yang adakalanya hadir dalam karya sastra Melayu Klasik. Pernyataan tersebut muncul dalam prolog dan atau epilog naskah. Ada beberapa kecenderungan motif yang melatarbelakangi kemuculannya. Motif tersebut dapat dilihat dari sudut pandang penyalin teks, sudut pandang teks, serta sudut pandang semesta. Motif ekonomi, motif syiar agama, motif akan pentingnya teks, serta motif terkait dengan situasi budaya dapat saja melatarbelakangi hadirnya pernyataan kalam tersebut dalam suatu karya sastra Melayu Klasik.---AbstractKalam statement is something that is sometimes present in classical Malay literature. The statement appears in the prologue or epilogue script. There are several trends motive behind kemuculannya. The motif can be seen from the viewpoint of copyists text, text viewing angle, and the angle of view of the universe. Economic motives, symbols of religious motives, motives of the importance of the text, as well as the motif associated with the cultural situation may be behind the presence of the kalam statement in a classical Malay literature.